Correlation of Serum Calcium with Acute Ischemic Stroke - Imran Qadir Khattak, Muhammad Fida, Romana Bibi, Arif Saleem, Rubab Khan, Muhammad Usman Afridi, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Stroke or cerebrovascular accident is the most common cause for disability and third leading cause of mortality worldwide. Stroke not only accounts for leading reason for mortality and morbidity, but also puts a great economic burden on the family as well as on society. Aim: To determine the relationship between blood calcium levels and the severity of patients with acute ischemic stroke presented to the medical department HMC Peshawar. Methodology: From July 2019 to January 2020, the Department of Medicine at the Hayatabad Medical Complex in Peshawar carried out this descriptive (cross-sectional) study. 137 patients fulfilling the inclusion criteria were selected for this study. Appropriate history regarding presenting neurological deficit, occupational and socioeconomic history were taken to dig out the confounding factors. After taking history, appropriate physical examination was performed study the relationship between blood calcium levels and the severity of acute ischemic stroke Results: Out of 137 patients, 71 were males and 66 females with age range of 35-80 years (Mean 56.42 years + 12.44SD). Pearson correlation coefficient shows that severity of stroke and serum calcium have negative correlation of -0.236. Majority of patients in our research sample had ischemic strokes, as evidenced by NIHSS scores of greater than 20, followed by scores of 6–10 individuals. To support the treatment recommendation of hypercalcemia in patient who presented with electrolyte imbalance should be treated early on time to prevent stroke and its severity. Conclusion: Smoking habits of the trial participants were evenly distributed amongst the intervention groups, and they had no impact on the outcome of patients with acute ischemic stroke. Patients with ischemic stroke consistently had lower blood calcium levels than non-diabetic patients with diabetes mellitus. In order to support the treatment advice for hypercalcemia, patients who first presented with electrolyte imbalance should receive therapy as soon as possible in order to reduce the risk of stroke and its severity. Keywords: Ischemic stroke, serum calcium, hypertension, diabetes mellitus.